Gingival overgrowth induced by anticonvulsant drugs: A cross‐sectional study on epileptic patients. (23rd December 2020) - Gallo, Claudio; Bonvento, Giada; Zagotto, Giuseppe; Mucignat‐Caretta, Carla
Abstract: Objective: Our aim was to estimate the prevalence of gingival overgrowth (hyperplasia) and to determine whether active molecules affect the severity of overgrowth in a group of epileptic patients. Background: The effects of phenytoin on oral health have been explored in different studies, yet little information is available on other antiepileptic drugs. Methods: Data were collected from 213 subjects of both sexes, from 5 to 80 years. Patients taking the same antiepileptic therapy for at least 1 year and meeting the inclusion criteria of the study (n = 162) were subjected to measurement of gingival overgrowth according to the modified Harris and Ewalt classification and O'Leary's plaque control record (OLR). Descriptive statistics were calculated. Data were analyzed using Pearson's r correlation coefficient and chi‐square test. Significance level was set at 5%. Results: The active drugs lamotrigine, oxcarbazepine, and phenobarbital were significantly associated with gingival overgrowth in 61%, 71%, and 53% of cases, respectively, and phenytoin, valproic acid, and carbamazepine in 50%, 44%, and 32% of cases, respectively. Conclusion: Different antiepileptic molecules may be related to gingival overgrowth. In addition to phenytoin, also lamotrigine, oxcarbazepine, and phenobarbital were associated with increased prevalence of gingival overgrowth. In the management of epileptic patients, dentists should take into account different drugs as possible causes for gingival overgrowth and warn for possible alternatives.